2020
DOI: 10.1523/jneurosci.1312-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Efferent Activity on Hair Bundle Mechanics

Abstract: Hair cells in both the auditory and vestibular systems receive efferent innervation. A number of prior studies have indicated that efferent regulation serves to diminish the overall sensitivity of the auditory system. The efferent pathway is believed to affect the sensitivity and frequency selectivity of the hair cell by modulating its membrane potential. However, its effect on the mechanical response of the hair cell has not been established. We explored how stimulation of the efferent neurons affects the mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 76 publications
2
8
0
Order By: Relevance
“…The saccular nerve was stimulated using a bipolar suction electrode (AM Systems; Lin and Bozovic, 2020 ) and electrically connected to the positive electrode via a 0.5 mm diameter silicon tube ( Castellano-Muñoz et al, 2010 ). The reference electrode was positioned in the basolateral compartment.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The saccular nerve was stimulated using a bipolar suction electrode (AM Systems; Lin and Bozovic, 2020 ) and electrically connected to the positive electrode via a 0.5 mm diameter silicon tube ( Castellano-Muñoz et al, 2010 ). The reference electrode was positioned in the basolateral compartment.…”
Section: Methodsmentioning
confidence: 99%
“…This active motility is sensitive to changes in Ca 2+ concentration, membrane potential of the soma, and other manipulations, and thus provides us with a useful experimental readout of the dynamic state of the hair bundle (Bozovic and Hudspeth, 2003;Martin et al, 2003;Le Goff et al, 2005;Ramunno-Johnson et al, 2010;Roongthumskul et al, 2011;Meenderink et al, 2015;Salvi et al, 2015;Lin and Bozovic, 2020). In this subsection, we report on the findings of experiments on saccular hair cells solely experiencing mechanical overstimulation, and examine its impact on the innate oscillations of the bundle.…”
Section: Hair Bundles Express Gradual Recuperation Following Mechanic...mentioning
confidence: 99%
See 1 more Smart Citation
“…The spontaneous oscillations, are chosen as candidate of active behavior of hair bundles in vitro to be studied Ramunno-Johnson et al (2010), due to that limitations of experimental conditions in vivo make the detection to the active behaviors in vivo is difficult. A large number of experiments have reported the existence and dynamics of spontaneous oscillations of hair bundles Barral et al (2018), Lin and Bozovic (2020), Roongthumskul et al (2021), which form the basis and manifestation of otoacoustic emission (Sound signals are detected in the ear under quiet conditions) detected in organisms. The detection and analysis of spontaneous oscillations are important ways to study auditory function in vitro Martin et al (2003).…”
Section: Introductionmentioning
confidence: 99%
“…In toadfish, electrical stimulation of efferents leads to an increase in the afferent resting discharge rate and to inhibition of hair cells, which is thought to result in the reduced gain of the afferent response to canal stimulation (Boyle et al 2009). Furthermore, it has been shown that efferent stimulation decreases the motility of vestibular hair cells in frogs (Castellano-Munoz et al 2010;Jessica Lin and Bozovic 2020) and toadfish (Rabbitt et al 2010), probably involved in the decrease in afferent sensitivities with efferent stimulation. Although such dynamic gain adjustments can theoretically be used to adjust the dynamic range of neurons (e.g., during fast self-generated head movements by toadfish), it has not been found in primates (Sadeghi et al 2007).…”
Section: Introductionmentioning
confidence: 99%